Modern office management. - Vohra,S.K; Vohra, S.K (New Delhi, Ansari Road Daryaganj, 2005)
Deals with office management, focusing on office layout, staffing, job descriptions, supervision, interoffice information flow, expanse controls, and records management.
includes bibliographic and index
eng
Keywords: Office management